Is There a Relation between EEG-Slow Waves and Memory Dysfunction in Epilepsy? A Critical Appraisal - Höller, Yvonne; Trinka, Eugen (Frontiers in Human Neuroscience, 2015)
Is there a relationship between peri-ictal slow waves, loss of consciousness, memory, and slow wave sleep, in patients with different forms of epilepsy? We hypothesize that mechanisms which result in peri-ictal slow wave activity as detected by the electroencephalogram could negatively affect memory processes. Slow waves (≤ 4 Hz) can be found in seizures with impairment of consciousness and also occur in focal seizures without impairment of consciousness but with inhibited access to memory functions. Peri-ictal slow waves are regarded as dysfunctional and are probably caused by mechanisms which are essential to disturb the consolidation of memory entries in these patients. This is in strong contrast to physiological slow wave activity during deep sleep, which is thought to group memory-consolidating fast oscillatory activity. In patients with epilepsy, slow waves may not only correlate with the peri-ictal clouding of consciousness, but could be the epiphenomenon of mechanisms which interfere with normal brain function in a wider range. These mechanisms may have transient impacts on memory, such as temporary inhibition of memory systems, altered patterns of hippocampal-neocortical interactions during slow wave sleep, or disturbed cross-frequency coupling of slow and fast oscillations. In addition, repeated tonic-clonic seizures over the years in uncontrolled chronic epilepsy may cause a progressive cognitive decline. This hypothesis can only be assessed in long term prospective studies. These studies could disentangle the reversible short-term impacts of seizures, and the impacts of chronic uncontrolled seizures. Chronic uncontrolled seizures lead to irreversible memory impairment. In contrast, short term impacts do not necessarily lead to a progressive cognitive decline but result in significantly impaired peri-ictal memory performance.